2021
DOI: 10.1108/scm-07-2020-0313
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the effect of supply chain disruption risk drivers on organizational performance: evidence from Chinese supply chains

Abstract: Purpose This paper aims to examine the relationship of supply chain disruption risk drivers to supply chain performance and firm performance outcomes. Design/methodology/approach Four disruption risk drivers for a supply chain are identified, namely, demand disruption risk, supply disruption risk, process disruption risk and environment disruption risk. A cross-sectional survey was developed and data was collected from 315 Chinese firms to determine the relationship of supply chain disruption risks to supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 83 publications
(139 reference statements)
2
79
2
Order By: Relevance
“…Extant literature has investigated the SCDR in two streams. The first stream examined SCDR as a multi-dimensional concept triggered by several internal and external drivers (Kleindorfer and Saad, 2005; Parast and Subramanian, 2021; Tse et al , 2016). Table 1 presents the summary of drivers of SCDR that are identified in the past literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant literature has investigated the SCDR in two streams. The first stream examined SCDR as a multi-dimensional concept triggered by several internal and external drivers (Kleindorfer and Saad, 2005; Parast and Subramanian, 2021; Tse et al , 2016). Table 1 presents the summary of drivers of SCDR that are identified in the past literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The demand risk measure captures the risk arising from changes in customer demand and market volatility during Covid-19 (Wagner and Bode, 2008;Chen et al, 2013;Ho et al, 2015;Parast and Subramanian, 2021). Similarly, SC risk encompasses risk from Covid-19 and its upstream SC actors, for instance, suppliers' performance (Wagner and Bode, 2008;Chen et al, 2013;Ho et al, 2015, Parast andSubramanian, 2021). Organisational productivity measures were adapted from Udofia et al, (2020).…”
Section: Survey Questionnaire Development and Structurementioning
confidence: 99%
“…The ongoing Covid-19 pandemic has created a new era worldwide and up to date many businesses still continue to understand the crippling effects it has on various aspects of their daily operations (Do et al, 2021). This virus revealed that events characterized by unprecedented uncertainty impinged on normal demand and supply patterns, causing a significant economic crisis, sales declines and disruptions in the supply chain (SC) system (Parast and Subramanian, 2021;Kumar and Abdin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As we are aware, COVID-19, which caused severe acute respiratory syndrome, was first identified in China in December 2019 . However, within a short span of time, the virus spread to other countries in Asia, Europe, and North America and was declared a pandemic by the World Health Organization (WHO) on 11 March 2020 Ivanov, 2020;Ivanov and Dolgui, 2020a;Shih, 2020;Parast and Subramanian, 2021). Due to the severe health crisis resulting from COVID-19, governments of affected countries are required to slow the spread of the virus by imposing containment and suppression measures Queiroz et al 2020;El Baaz and Ruel, 2020;Sodhi and Tang, 2021;Belhadi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…and North America and was declared a pandemic by the World Health Organization on March 11, 2020 Ivanov, 2020;Ivanov and Dolgui, 2020a;Shih, 2020;Parast and Subramanian, 2021). Due to the severe health crisis resulting from COVID-19, governments of affected countries are required to slow the spread of the virus by imposing containment and suppression measures Queiroz et al, 2020;El Baz and Ruel, 2021;Sodhi and Tang, 2021;Belhadi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%